Developing creative service ideas through hotel customer engagement for open innovation: Focused on empowerment and motivation processes. (January 2022) - Shin, Hakseung; Perdue, Richard R.
Abstract: While the enhanced connectivity between customers and hospitality brands via online platforms dramatically increases the potential for customer engagement in innovation processes, existing research has not focused on how to facilitate open innovation knowledge creation via customer engagement. The purpose of this research is to explore open innovation processes by examining the impact of customer empowerment and social recognition rewards on both open innovation engagement intentions and the creativity of proposed innovation ideas. Two scenario-based experimental studies and a field survey were conducted. The studies found that customer empowerment, mediated by intrinsic motivations, increased open innovation engagement intentions and also had a positive effect on the creativity of proposed innovation ideas. Social recognition rewards, as a form of extrinsic motivation, did not contribute to either open innovation engagement intentions or the creativity of innovation ideas. This empowerment-intrinsic motivational process for open innovation engagement was confirmed in a field survey. Highlights: Empowered hotel customers are likely to share service ideas for open innovation. Customer empowerment has a positive impact on creativity of innovation ideas. Pure enjoyment is the main driver of knowledge sharing behaviors for open innovation. Social recognition has no influence on open innovation engagement. Online brand community is an ideal platform for hospitality open innovation.